Application of an Automatic Suction Device to a Patient with A Tracheostomy Tube in the General Ward: A Case Report - Sehyeon Yu; Hanyoung Lee; Jae-Myeong Lee (Journal of Acute Care Surgery)
The A-1000 (Elmeca, Co. Ltd., Seoul, Korea) electrical automatic airway suction device, was designed to operate as a customizable repeated closed suction device. It can be used for patients with intubation or tracheostomy tubes. This is the first recorded case of the use of the A-1000 in a general ward patient with a tracheostomy tube. A 91-year-old man presented having attempted suicide by hanging and was admitted to this institution. Although extubation was performed in the intensive care unit, the patient required 2 reintubations. The tracheostomy was performed, and the A-1000 was applied. After weaning from mechanical ventilation, the patient was transferred to the General Ward with a tracheostomy tube in place for effective removal of sputum by the A-1000. The tracheostomy tube was successfully removed, and the patient was discharged. The effectiveness and safety of the A-1000 needs further study by expanding the applications of this device.